2015
DOI: 10.1037/pas0000079
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric analysis of the BASC–2 Behavioral and Emotional Screening System (BESS) student form: Results from high school student samples.

Abstract: The Behavioral and Emotional Screening System (BESS) is a relatively new method for identifying behavior and emotional risk (BER) in children and adolescents. Psychometric evidence regarding this instrument is important for researchers and practitioners considering the use of the BESS for identifying BER in students. Previous psychometric research specifically regarding the BESS Student Form involved the use of samples of elementary and middle school-age children. This study adds to the psychometric evidence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
5
13
0
Order By: Relevance
“…Results of this study indicated that the BESS items fell into the four factors from which they were initially drawn (personal adjustment, school problems, internalizing problems, and inattention/hyperactivity). Harrell-Williams et al (2015) were able to confirm this factor structure and establish measurement equivalence across ethnic groups (African American, Hispanic, White, and Other) in work with high school students from urban schools in California and Georgia, as well as a sample drawn from the BESS norming group. While this work with the student form provides preliminary evidence for the existence of a multidimensional model, failure to test for a hierarchical structure misses the potential contribution of a global risk score.…”
Section: Modeling Strategies For Assessing the Bess Factor Structurementioning
confidence: 74%
See 3 more Smart Citations
“…Results of this study indicated that the BESS items fell into the four factors from which they were initially drawn (personal adjustment, school problems, internalizing problems, and inattention/hyperactivity). Harrell-Williams et al (2015) were able to confirm this factor structure and establish measurement equivalence across ethnic groups (African American, Hispanic, White, and Other) in work with high school students from urban schools in California and Georgia, as well as a sample drawn from the BESS norming group. While this work with the student form provides preliminary evidence for the existence of a multidimensional model, failure to test for a hierarchical structure misses the potential contribution of a global risk score.…”
Section: Modeling Strategies For Assessing the Bess Factor Structurementioning
confidence: 74%
“…The schools that these data were retrieved from enrolled between 87% and 98% African American, low-income students; therefore, we were unable to conduct a test of measurement equivalence. However, considering that measurement invariance was evaluated in the creation of the BESS (Kamphaus & Reynolds, 2007) and has been established in an independent sample for the BESS SF (Harrell-Williams et al, 2015), we were interested in replicating the factor structure of the BESS SF looking at within-group instead of between-group functioning. Confirming the factor structures in this sample paves the way for future research linking these factor structures to relevant outcomes for schools that serve predominantly low-income, African American youth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, teacher reports of preschooler’s self-regulatory behavior (McCoy et al, 2011) and youth self-reports of behavioral and emotional functioning (Harrell-Williams et al, 2015) were demonstrated to be invariant across racial and income groups. In other studies, partial invariance has been demonstrated across racial groups on youth self-reports of anxiety and depression (Holly et al, 2015; Trent et al, 2012).…”
Section: Rationale For the Current Studymentioning
confidence: 99%